Effect of Dividend Policy and Leverage on Sustainable Growth Moderated by Managerial Ownership in Energy Sector Companies - Sri Hartatik; Indarto Indarto; Rohmini Indah Lestari (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study aims to analyze the effect of dividend policy and leverage on the company's sustainable growth, with managerial ownership as a moderating variable. The dependent variable is the company's sustainable growth, while the independent variables are dividend policy and leverage. Secondary data were obtained from the financial statements of energy sector companies listed on the IDX for the period 2019-2023. This study uses a purposive sampling technique with a sample size of 7 companies. The analysis was carried out using panel data regression with Eviews 13 software. The results of the study indicate that dividend policy and leverage do not have a significant effect on the company's sustainable growth. In addition, managerial ownership does not moderate the relationship between dividend policy and leverage on the company's sustainable growth. This finding indicates that other factors may play a greater role in determining the sustainable growth of energy sector companies. Therefore, further research is needed by considering other variables that can affect company growth, such as profitability, ownership structure, and macroeconomic conditions, to gain a more comprehensive understanding of the factors that drive sustainable growth in the energy sector.